PENGARUH AKUNTABILITAS,INDEPENDENSI,KOMPETENSI, OBEKTIVITAS DAN INTEGRITAS TERHADAP KUALITAS HASILKERJA AUDITOR (Studi Empiris Pada Kantor Akuntan Publik di Kota Semarang) - Anisatun Nihayah, 13.05.52.0225; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2018)
Nowday, more and more people from all walks of life need reliable corporate financial statements. That is the responsibility of a public accountant or known as an auditor to improve the reliability of financial statements. Therefore, qualified auditors need to audit the financial statements. This study aims to examine the effect of accountability, independence, competence, objectivity, and integrity on audit work quality. The object of this research is Public Accounting Firm in Semarang City. This research uses random sampling technique in data collection. Respondents in this study are all auditors in the Public Accounting Firm in Semarang City, which amounted to 52 respondents. There are five variables in this study consisting of five independent variables namely accountability, independence, competence, objectivity, integrity, and one dependent variable is the quality of the auditor's work. Based on the result of this research, it can be concluded that some of accountability, independence, competence, and integrity have a significant effect on the quality of audit work, while independence and objectivity have an effect on audit quality but not significant. Simultaneously, independence, competence, work experience, objectivity and integrity affect the quality of audit workKeywords: Accountability, Independence, Competence, Objectivity, Integrity, Audit Quality